2007
DOI: 10.1002/app.26687
|View full text |Cite
|
Sign up to set email alerts
|

Radical scavenging capacity of lignin and its effect on processing stabilization of virgin and recycled polypropylene

Abstract: ABSTRACT:The radical scavenging capacity of lignin was determined using spectrophotometric method by means of scavenging of the free radical 2,2-diphenyl-1-picrylhydrazyl (DPPH ) and compared with that of synthetic antioxidant Irganox 1010. Lignin reacted progressively with the DPPH reaching a steady state in 6 h, showing high antiradical activity with a stochiometry of 5.5 reduced DPPH molecules. Irganox 1010 showed lower antiradical activity reaching a steady state with DPPH after 13 h. Moreover, stabilizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 22 publications
1
41
0
Order By: Relevance
“…In the field of material applications, the antioxidant activity has been investigated in the aim of using lignin as a natural substitute of synthetic antioxidants required for the formulation of polyolefins [22][23][24][25]. Pouteau et al [26] showed that the compatibility between lignin and polymer matrix could be successfully predicted using the solubility parameters calculated after the Small, Van Krevelen and Hoy method.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of material applications, the antioxidant activity has been investigated in the aim of using lignin as a natural substitute of synthetic antioxidants required for the formulation of polyolefins [22][23][24][25]. Pouteau et al [26] showed that the compatibility between lignin and polymer matrix could be successfully predicted using the solubility parameters calculated after the Small, Van Krevelen and Hoy method.…”
Section: Introductionmentioning
confidence: 99%
“…One of them is related to the presence of lignocellulosic filler in the polymer matrix, which imparts stability to the composite materials by the presence of lignin acting as natural antioxidants. As a matter of fact, some authors [31] Effect of Reprocessing Cycles on the Morphology and . .…”
Section: Resultsmentioning
confidence: 99%
“…The results suggest that the PP material should not be recycled more than one time. According to the literature, [17,[29][30][31] behavior is due to degradation by chain scission giving rise to a significant decrease in molecular weight and subsequently to lower viscosity. The combination of high temperature, shear and the presence of oxygen and chromophoric species such as hydroperoxides, carbonyl groups and catalyst residues in the polymer matrix, could be the main factors promoting degradation.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…Most of the attempts proved the antioxidant effect of lignin. The antioxidant and stabilizing characteristics of lignin have been studied in several polymers, but mainly in PE [153][154][155][156], PP [153,[157][158][159][160][161][162][163][164], PLA [165,166], poly(3-hydroxybutyrate) (PHB) [167], PCL [168] and in natural rubber [169,170].…”
Section: Application In Polymersmentioning
confidence: 99%